Ventricular ectopic beats in structurally normal heart: When to stop investigations - Zangana, Sabah Z. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background & Objectives: Ventricular ectopic beats (extra systoles, premature beats) are frequently found in healthy people. Ectopic beats in patients without apparent heart disease are more prominent at rest and disappear with exercise. Treatment is not necessary unless the patient is highly symptomatic. Methods: Patients having ventricular ectopic beats were assessed clinically, by ECG and by echocardiography. Those with normal structure hearts underwent exercise ECG and among those we selected 50 patients whose ectopics were suppressed by exercise then followed them for 5 years. The study started from 2000 to 2010. Results: During 5-year follow-up of the above mentioned patients, relevant complications such as dangerous ventricular arrhythmias, ischemic heart diseases or heart failure were not recorded. Conclusions: In patients having ventricular ectopic beats and structurally normal heart, the suppressibilty of the ectopic by exercise indicated their benign origin and may preclude further invasive investigations and even specific treatment.